------------------------------------------------------------------------
-- Bag equivalence for lists
------------------------------------------------------------------------
{-# OPTIONS --without-K #-}
-- Note that this module is not parametrised by a definition of
-- equality; it uses ordinary propositional equality.
module Bag-equivalence where
open import Equality.Propositional hiding (trans)
open import Fin
open import Logical-equivalence hiding (id; _∘_; inverse)
open import Prelude as P hiding (id)
open import Bijection equality-with-J using (_↔_; module _↔_; Σ-≡,≡↔≡)
open import Equality.Decision-procedures equality-with-J
open import Function-universe equality-with-J as Function-universe
hiding (_∘_; Kind; module Kind; bijection)
open import Injection equality-with-J using (_↣_)
------------------------------------------------------------------------
-- Any
-- Any.
Any : ∀ {a p} {A : Set a} (P : A → Set p) (xs : List A) → Set p
Any P [] = ⊥
Any P (x ∷ xs) = P x ⊎ Any P xs
-- Alternative definition of Any.
data Any′ {a p} {A : Set a}
(P : A → Set p) : List A → Set (a ⊔ p) where
here : ∀ {x xs} → P x → Any′ P (x ∷ xs)
there : ∀ {x xs} → Any′ P xs → Any′ P (x ∷ xs)
-- The two definitions of Any are isomorphic.
Any′-[] : ∀ {a p ℓ} {A : Set a} {P : A → Set p} →
Any′ P [] ↔ ⊥ {ℓ = ℓ}
Any′-[] {ℓ = ℓ} {P = P} = record
{ surjection = record
{ logical-equivalence = record
{ to = to
; from = from
}
; right-inverse-of = λ p → ⊥-elim p
}
; left-inverse-of = from∘to
}
where
to′ : ∀ {xs} → Any′ P xs → [] ≡ xs → ⊥ {ℓ = ℓ}
to′ (here p) = ⊥-elim ∘ List.[]≢∷
to′ (there p) = ⊥-elim ∘ List.[]≢∷
to : Any′ P [] → ⊥
to p = to′ p refl
from = ⊥-elim
from∘to′ : ∀ {xs} (p : Any′ P xs) ([]≡xs : [] ≡ xs) →
subst (Any′ P) []≡xs (from (to′ p []≡xs)) ≡ p
from∘to′ (here p) = ⊥-elim ∘ List.[]≢∷
from∘to′ (there p) = ⊥-elim ∘ List.[]≢∷
from∘to : ∀ p → from (to p) ≡ p
from∘to p = from∘to′ p refl
Any′-∷ : ∀ {a p} {A : Set a} {P : A → Set p} {x xs} →
Any′ P (x ∷ xs) ↔ P x ⊎ Any′ P xs
Any′-∷ {P = P} {x} {xs} = record
{ surjection = record
{ logical-equivalence = record
{ to = to
; from = from
}
; right-inverse-of = [ (λ _ → refl) , (λ _ → refl) ]
}
; left-inverse-of = from∘to
}
where
to′ : ∀ {ys} → Any′ P ys → ys ≡ x ∷ xs → P x ⊎ Any′ P xs
to′ (here p) ≡∷ = inj₁ (subst P (List.cancel-∷-head ≡∷) p)
to′ (there p) ≡∷ = inj₂ (subst (Any′ P) (List.cancel-∷-tail ≡∷) p)
to : Any′ P (x ∷ xs) → P x ⊎ Any′ P xs
to p = to′ p refl
from = [ here , there ]
from∘to′ : ∀ {ys} (p : Any′ P ys) ≡∷ →
from (to′ p ≡∷) ≡ subst (Any′ P) ≡∷ p
from∘to′ (here p) ≡∷ with List.cancel-∷-head ≡∷
| List.cancel-∷-tail ≡∷
| sym (List.unfold-∷ ≡∷)
from∘to′ (here p) .refl | refl | refl | refl = refl
from∘to′ (there p) ≡∷ with List.cancel-∷-head ≡∷
| List.cancel-∷-tail ≡∷
| sym (List.unfold-∷ ≡∷)
from∘to′ (there p) .refl | refl | refl | refl = refl
from∘to : ∀ p → from (to p) ≡ p
from∘to p = from∘to′ p refl
Any↔Any′ : ∀ {a p} {A : Set a} {P : A → Set p} {xs} →
Any P xs ↔ Any′ P xs
Any↔Any′ {P = P} {[]} =
⊥ ↔⟨ inverse Any′-[] ⟩
Any′ P [] □
Any↔Any′ {P = P} {x ∷ xs} =
P x ⊎ Any P xs ↔⟨ id ⊎-cong Any↔Any′ {P = P} ⟩
P x ⊎ Any′ P xs ↔⟨ inverse Any′-∷ ⟩
Any′ P (x ∷ xs) □
------------------------------------------------------------------------
-- Lemmas relating Any to some basic list functions
Any-++ : ∀ {a p} {A : Set a} (P : A → Set p) (xs ys : List A) →
Any P (xs ++ ys) ↔ Any P xs ⊎ Any P ys
Any-++ P [] ys =
Any P ys ↔⟨ inverse ⊎-left-identity ⟩
⊥ ⊎ Any P ys □
Any-++ P (x ∷ xs) ys =
P x ⊎ Any P (xs ++ ys) ↔⟨ id ⊎-cong Any-++ P xs ys ⟩
P x ⊎ (Any P xs ⊎ Any P ys) ↔⟨ ⊎-assoc ⟩
(P x ⊎ Any P xs) ⊎ Any P ys □
Any-concat : ∀ {a p} {A : Set a}
(P : A → Set p) (xss : List (List A)) →
Any P (concat xss) ↔ Any (Any P) xss
Any-concat P [] = id
Any-concat P (xs ∷ xss) =
Any P (xs ++ concat xss) ↔⟨ Any-++ P xs (concat xss) ⟩
Any P xs ⊎ Any P (concat xss) ↔⟨ id ⊎-cong Any-concat P xss ⟩
Any P xs ⊎ Any (Any P) xss □
Any-map : ∀ {a b p} {A : Set a} {B : Set b}
(P : B → Set p) (f : A → B) (xs : List A) →
Any P (map f xs) ↔ Any (P ∘ f) xs
Any-map P f [] = id
Any-map P f (x ∷ xs) =
P (f x) ⊎ Any P (map f xs) ↔⟨ id ⊎-cong Any-map P f xs ⟩
(P ∘ f) x ⊎ Any (P ∘ f) xs □
Any->>= : ∀ {a b p} {A : Set a} {B : Set b}
(P : B → Set p) (xs : List A) (f : A → List B) →
Any P (xs >>= f) ↔ Any (Any P ∘ f) xs
Any->>= P xs f =
Any P (concat (map f xs)) ↔⟨ Any-concat P (map f xs) ⟩
Any (Any P) (map f xs) ↔⟨ Any-map (Any P) f xs ⟩
Any (Any P ∘ f) xs □
Any-filter : ∀ {a p} {A : Set a}
(P : A → Set p) (p : A → Bool) (xs : List A) →
Any P (filter p xs) ↔ Any (λ x → P x × T (p x)) xs
Any-filter P p [] = ⊥ □
Any-filter P p (x ∷ xs) with p x
... | true =
P x ⊎ Any P (filter p xs) ↔⟨ inverse ×-right-identity ⊎-cong Any-filter P p xs ⟩
(P x × ⊤) ⊎ Any (λ x → P x × T (p x)) xs □
... | false =
Any P (filter p xs) ↔⟨ Any-filter P p xs ⟩
Any (λ x → P x × T (p x)) xs ↔⟨ inverse ⊎-left-identity ⟩
⊥₀ ⊎ Any (λ x → P x × T (p x)) xs ↔⟨ inverse ×-right-zero ⊎-cong (_ □) ⟩
(P x × ⊥) ⊎ Any (λ x → P x × T (p x)) xs □
------------------------------------------------------------------------
-- List membership
infix 4 _∈_
_∈_ : ∀ {a} {A : Set a} → A → List A → Set _
x ∈ xs = Any (λ y → x ≡ y) xs
-- Any can be expressed using _∈_.
Any-∈ : ∀ {a p} {A : Set a} (P : A → Set p) (xs : List A) →
Any P xs ↔ ∃ λ x → P x × x ∈ xs
Any-∈ P [] =
⊥ ↔⟨ inverse ×-right-zero ⟩
(∃ λ x → ⊥₀) ↔⟨ ∃-cong (λ x → inverse ×-right-zero) ⟩
(∃ λ x → P x × ⊥) □
Any-∈ P (x ∷ xs) =
P x ⊎ Any P xs ↔⟨ ∃-intro P x ⊎-cong Any-∈ P xs ⟩
(∃ λ y → P y × y ≡ x) ⊎ (∃ λ y → P y × y ∈ xs) ↔⟨ inverse ∃-⊎-distrib-left ⟩
(∃ λ y → P y × y ≡ x ⊎ P y × y ∈ xs) ↔⟨ ∃-cong (λ y → inverse ×-⊎-distrib-left) ⟩
(∃ λ y → P y × (y ≡ x ⊎ y ∈ xs)) □
-- Using this property we can prove that Any and _⊎_ commute.
Any-⊎ : ∀ {a p q} {A : Set a}
(P : A → Set p) (Q : A → Set q) (xs : List A) →
Any (λ x → P x ⊎ Q x) xs ↔ Any P xs ⊎ Any Q xs
Any-⊎ P Q xs =
Any (λ x → P x ⊎ Q x) xs ↔⟨ Any-∈ (λ x → P x ⊎ Q x) xs ⟩
(∃ λ x → (P x ⊎ Q x) × x ∈ xs) ↔⟨ ∃-cong (λ x → ×-⊎-distrib-right) ⟩
(∃ λ x → P x × x ∈ xs ⊎ Q x × x ∈ xs) ↔⟨ ∃-⊎-distrib-left ⟩
(∃ λ x → P x × x ∈ xs) ⊎ (∃ λ x → Q x × x ∈ xs) ↔⟨ inverse $ Any-∈ P xs ⊎-cong Any-∈ Q xs ⟩
Any P xs ⊎ Any Q xs □
------------------------------------------------------------------------
-- Bag and set equivalence and the subset and subbag orders
-- Various kinds of relatedness.
open Function-universe public using (Kind)
module Kind where
open Function-universe public
using ()
renaming ( implication to subset
; logical-equivalence to set
; injection to subbag
; bijection to bag
; equivalence to bag-with-equivalence
)
open Kind public
-- A general definition of "relatedness" for lists.
infix 4 _∼[_]_
_∼[_]_ : ∀ {a} {A : Set a} → List A → Kind → List A → Set a
xs ∼[ k ] ys = ∀ z → z ∈ xs ↝[ k ] z ∈ ys
-- Bag equivalence.
infix 4 _≈-bag_
_≈-bag_ : ∀ {a} {A : Set a} → List A → List A → Set a
xs ≈-bag ys = xs ∼[ bag ] ys
-- Alternative definition of bag equivalence.
infix 4 _≈-bag′_
record _≈-bag′_ {a} {A : Set a} (xs ys : List A) : Set a where
field
bijection : Fin (length xs) ↔ Fin (length ys)
related : xs And ys Are-related-by bijection
-- Yet another definition of bag equivalence. This definition is taken
-- from Coq's standard library.
infixr 5 _∷_
infix 4 _≈-bag″_
data _≈-bag″_ {a} {A : Set a} : List A → List A → Set a where
[] : [] ≈-bag″ []
_∷_ : ∀ x {xs ys} (xs≈ys : xs ≈-bag″ ys) → x ∷ xs ≈-bag″ x ∷ ys
swap : ∀ {x y xs} → x ∷ y ∷ xs ≈-bag″ y ∷ x ∷ xs
trans : ∀ {xs ys zs}
(xs≈ys : xs ≈-bag″ ys) (ys≈zs : ys ≈-bag″ zs) → xs ≈-bag″ zs
------------------------------------------------------------------------
-- Some congruence lemmas
Any-cong : ∀ {k a p q} {A : Set a}
{P : A → Set p} {Q : A → Set q} {xs ys : List A} →
(∀ x → P x ↝[ k ] Q x) → xs ∼[ k ] ys →
Any P xs ↝[ k ] Any Q ys
Any-cong {P = P} {Q} {xs} {ys} P↔Q xs≈ys =
Any P xs ↔⟨ Any-∈ P xs ⟩
(∃ λ z → P z × z ∈ xs) ↝⟨ ∃-cong (λ z → P↔Q z ×-cong xs≈ys z) ⟩
(∃ λ z → Q z × z ∈ ys) ↔⟨ inverse (Any-∈ Q ys) ⟩
Any Q ys □
++-cong : ∀ {k a} {A : Set a} {xs₁ xs₂ ys₁ ys₂ : List A} →
xs₁ ∼[ k ] ys₁ → xs₂ ∼[ k ] ys₂ →
xs₁ ++ xs₂ ∼[ k ] ys₁ ++ ys₂
++-cong {xs₁ = xs₁} {xs₂} {ys₁} {ys₂} xs₁∼ys₁ xs₂∼ys₂ = λ z →
z ∈ xs₁ ++ xs₂ ↔⟨ Any-++ _ xs₁ xs₂ ⟩
z ∈ xs₁ ⊎ z ∈ xs₂ ↝⟨ xs₁∼ys₁ z ⊎-cong xs₂∼ys₂ z ⟩
z ∈ ys₁ ⊎ z ∈ ys₂ ↔⟨ inverse (Any-++ _ ys₁ ys₂) ⟩
z ∈ ys₁ ++ ys₂ □
map-cong : ∀ {k a b} {A : Set a} {B : Set b}
(f : A → B) {xs ys : List A} →
xs ∼[ k ] ys → map f xs ∼[ k ] map f ys
map-cong f {xs} {ys} xs∼ys = λ z →
z ∈ map f xs ↔⟨ Any-map _ f xs ⟩
Any (λ x → z ≡ f x) xs ↝⟨ Any-cong (λ x → z ≡ f x □) xs∼ys ⟩
Any (λ x → z ≡ f x) ys ↔⟨ inverse (Any-map _ f ys) ⟩
z ∈ map f ys □
concat-cong : ∀ {k a} {A : Set a} {xss yss : List (List A)} →
xss ∼[ k ] yss → concat xss ∼[ k ] concat yss
concat-cong {xss = xss} {yss} xss∼yss = λ z →
z ∈ concat xss ↔⟨ Any-concat _ xss ⟩
Any (λ zs → z ∈ zs) xss ↝⟨ Any-cong (λ zs → z ∈ zs □) xss∼yss ⟩
Any (λ zs → z ∈ zs) yss ↔⟨ inverse (Any-concat _ yss) ⟩
z ∈ concat yss □
>>=-cong : ∀ {k a b} {A : Set a} {B : Set b}
{xs ys : List A} {f g : A → List B} →
xs ∼[ k ] ys → (∀ x → f x ∼[ k ] g x) →
(xs >>= f) ∼[ k ] (ys >>= g)
>>=-cong {xs = xs} {ys} {f} {g} xs∼ys f∼g = λ z →
z ∈ xs >>= f ↔⟨ Any->>= _ xs f ⟩
Any (λ x → z ∈ f x) xs ↝⟨ Any-cong (λ x → f∼g x z) xs∼ys ⟩
Any (λ x → z ∈ g x) ys ↔⟨ inverse (Any->>= _ ys g) ⟩
z ∈ ys >>= g □
filter-cong : ∀ {k a} {A : Set a} (p : A → Bool) (xs ys : List A) →
xs ∼[ k ] ys → filter p xs ∼[ k ] filter p ys
filter-cong p xs ys xs∼ys = λ z →
z ∈ filter p xs ↔⟨ Any-filter _ p xs ⟩
Any (λ x → z ≡ x × T (p x)) xs ↝⟨ Any-cong (λ _ → _ □) xs∼ys ⟩
Any (λ x → z ≡ x × T (p x)) ys ↔⟨ inverse (Any-filter _ p ys) ⟩
z ∈ filter p ys □
------------------------------------------------------------------------
-- More properties
-- Bind distributes from the left over append.
>>=-left-distributive :
∀ {a b} {A : Set a} {B : Set b} (xs : List A) (f g : A → List B) →
xs >>= (λ x → f x ++ g x) ≈-bag (xs >>= f) ++ (xs >>= g)
>>=-left-distributive xs f g = λ z →
z ∈ xs >>= (λ x → f x ++ g x) ↔⟨ Any->>= (_≡_ z) xs (λ x → f x ++ g x) ⟩
Any (λ x → z ∈ f x ++ g x) xs ↔⟨ Any-cong (λ x → Any-++ (_≡_ z) (f x) (g x)) (λ _ → id) ⟩
Any (λ x → z ∈ f x ⊎ z ∈ g x) xs ↔⟨ Any-⊎ (λ x → z ∈ f x) (λ x → z ∈ g x) xs ⟩
Any (λ x → z ∈ f x) xs ⊎ Any (λ x → z ∈ g x) xs ↔⟨ inverse (Any->>= (_≡_ z) xs f ⊎-cong Any->>= (_≡_ z) xs g) ⟩
z ∈ xs >>= f ⊎ z ∈ xs >>= g ↔⟨ inverse (Any-++ (_≡_ z) (xs >>= f) (xs >>= g)) ⟩
z ∈ (xs >>= f) ++ (xs >>= g) □
-- This property does not hold for ordinary list equality.
¬->>=-left-distributive :
¬ ({A B : Set} (xs : List A) (f g : A → List B) →
xs >>= (λ x → f x ++ g x) ≡ (xs >>= f) ++ (xs >>= g))
¬->>=-left-distributive distrib = Bool.true≢false true≡false
where
xs = true ∷ false ∷ []
f = λ x → x ∷ []
g = f
eq : true ∷ true ∷ false ∷ false ∷ [] ≡
true ∷ false ∷ true ∷ false ∷ []
eq = distrib xs f g
true≡false : true ≡ false
true≡false = List.cancel-∷-head (List.cancel-∷-tail eq)
-- _++_ is commutative.
++-comm : ∀ {a} {A : Set a} (xs ys : List A) → xs ++ ys ≈-bag ys ++ xs
++-comm xs ys = λ z →
z ∈ xs ++ ys ↔⟨ Any-++ (_≡_ z) xs ys ⟩
z ∈ xs ⊎ z ∈ ys ↔⟨ ⊎-comm ⟩
z ∈ ys ⊎ z ∈ xs ↔⟨ inverse (Any-++ (_≡_ z) ys xs) ⟩
z ∈ ys ++ xs □
-- _++_ is idempotent (when set equivalence is used).
++-idempotent : ∀ {a} {A : Set a} (xs : List A) → xs ++ xs ∼[ set ] xs
++-idempotent xs = λ z →
z ∈ xs ++ xs ↔⟨ Any-++ (_≡_ z) xs xs ⟩
z ∈ xs ⊎ z ∈ xs ↝⟨ ⊎-idempotent ⟩
z ∈ xs □
-- The so-called "range splitting" property (see, for instance,
-- Hoogendijks "(Relational) Programming Laws in the Boom Hierarchy of
-- Types").
range-splitting : ∀ {a} {A : Set a} (p : A → Bool) (xs : List A) →
filter p xs ++ filter (not ∘ p) xs ≈-bag xs
range-splitting p xs = λ z →
z ∈ filter p xs ++ filter (not ∘ p) xs ↔⟨ Any-++ _ _ (filter (not ∘ p) xs) ⟩
z ∈ filter p xs ⊎ z ∈ filter (not ∘ p) xs ↔⟨ Any-filter _ p xs ⊎-cong Any-filter _ (not ∘ p) xs ⟩
Any (λ x → z ≡ x × T (p x)) xs ⊎
Any (λ x → z ≡ x × T (not (p x))) xs ↔⟨ inverse $ Any-⊎ _ _ xs ⟩
Any (λ x → z ≡ x × T (p x) ⊎ z ≡ x × T (not (p x))) xs ↔⟨ Any-cong (λ x → lemma (z ≡ x) (p x)) (λ x → x ∈ xs □) ⟩
z ∈ xs □
where
lemma : ∀ {a} (A : Set a) (b : Bool) → A × T b ⊎ A × T (not b) ↔ A
lemma A b =
A × T b ⊎ A × T (not b) ↔⟨ ×-comm ⊎-cong ×-comm ⟩
T b × A ⊎ T (not b) × A ↔⟨ if-lemma (λ _ → A) id id b ⟩
A □
-- The so-called "range disjunction" property, strengthened to use the
-- subbag preorder instead of set equivalence.
range-disjunction :
∀ {a} {A : Set a} (p q : A → Bool) (xs : List A) →
filter (λ x → p x ∨ q x) xs ∼[ subbag ]
filter p xs ++ filter q xs
range-disjunction p q xs = λ z →
z ∈ filter (λ x → p x ∨ q x) xs ↔⟨ Any-filter _ (λ x → p x ∨ q x) _ ⟩
Any (λ x → z ≡ x × T (p x ∨ q x)) xs ↝⟨ Any-cong (λ x → lemma (z ≡ x) (p x) (q x)) (λ x → x ∈ xs □) ⟩
Any (λ x → z ≡ x × T (p x) ⊎ z ≡ x × T (q x)) xs ↔⟨ Any-⊎ _ _ _ ⟩
Any (λ x → z ≡ x × T (p x)) xs ⊎ Any (λ x → z ≡ x × T (q x)) xs ↔⟨ inverse (Any-filter _ p _ ⊎-cong Any-filter _ q _) ⟩
z ∈ filter p xs ⊎ z ∈ filter q xs ↔⟨ inverse $ Any-++ _ _ _ ⟩
z ∈ filter p xs ++ filter q xs □
where
inj : (b₁ b₂ : Bool) → T (b₁ ∨ b₂) ↣ T b₁ ⊎ T b₂
inj true true = record { to = inj₁; injective = λ _ → refl }
inj true false = record { to = inj₁; injective = ⊎.cancel-inj₁ }
inj false true = record { to = inj₂; injective = ⊎.cancel-inj₂ }
inj false false = record { to = λ (); injective = λ {} }
lemma : ∀ {a} (A : Set a) (b₁ b₂ : Bool) →
A × T (b₁ ∨ b₂) ↣ A × T b₁ ⊎ A × T b₂
lemma A b₁ b₂ =
A × T (b₁ ∨ b₂) ↝⟨ id ×-cong inj b₁ b₂ ⟩
A × (T b₁ ⊎ T b₂) ↔⟨ ×-⊎-distrib-left ⟩
A × T b₁ ⊎ A × T b₂ □
------------------------------------------------------------------------
-- The first two definitions of bag equivalence above are logically
-- equivalent
-- One direction follows from the following lemma, which states that
-- list membership can be expressed as "there is an index which points
-- to the element".
--
-- As an aside, note that the right-hand side is almost
-- lookup xs ⁻¹ z.
∈-lookup : ∀ {a} {A : Set a} {z}
(xs : List A) → z ∈ xs ↔ ∃ λ i → z ≡ lookup xs i
∈-lookup {z = z} [] =
⊥ ↔⟨ inverse $ ∃-Fin-zero _ ⟩
(∃ λ (i : ⊥) → z ≡ lookup [] i) □
∈-lookup {z = z} (x ∷ xs) =
z ≡ x ⊎ z ∈ xs ↔⟨ id ⊎-cong ∈-lookup xs ⟩
z ≡ x ⊎ (∃ λ i → z ≡ lookup xs i) ↔⟨ inverse $ ∃-Fin-suc _ ⟩
(∃ λ i → z ≡ lookup (x ∷ xs) i) □
-- The index which points to the element.
index : ∀ {a} {A : Set a} {z} {xs : List A} → z ∈ xs → Fin (length xs)
index = proj₁ ∘ _↔_.to (∈-lookup _)
-- For the other direction a sequence of lemmas is used.
-- The first lemma states that ∃ λ z → z ∈ xs is isomorphic to Fin n,
-- where n is the length of xs. Thierry Coquand pointed out that this
-- is a generalisation of singleton-contractible.
Fin-length : ∀ {a} {A : Set a}
(xs : List A) → (∃ λ z → z ∈ xs) ↔ Fin (length xs)
Fin-length xs =
(∃ λ z → z ∈ xs) ↔⟨ ∃-cong (λ _ → ∈-lookup xs) ⟩
(∃ λ z → ∃ λ i → z ≡ lookup xs i) ↔⟨ ∃-comm ⟩
(∃ λ i → ∃ λ z → z ≡ lookup xs i) ↔⟨⟩
(∃ λ i → Singleton (lookup xs i)) ↔⟨ ∃-cong (λ _ → contractible↔⊤ (singleton-contractible _)) ⟩
Fin (length xs) × ⊤ ↔⟨ ×-right-identity ⟩
Fin (length xs) □
-- From this lemma we get that lists which are bag equivalent have
-- related lengths.
Fin-length-cong : ∀ {a} {A : Set a} {xs ys : List A} →
xs ≈-bag ys → Fin (length xs) ↔ Fin (length ys)
Fin-length-cong {xs = xs} {ys} xs≈ys =
Fin (length xs) ↔⟨ inverse $ Fin-length xs ⟩
∃ (λ z → z ∈ xs) ↔⟨ ∃-cong xs≈ys ⟩
∃ (λ z → z ∈ ys) ↔⟨ Fin-length ys ⟩
Fin (length ys) □
abstract
-- In fact, they have equal lengths.
length-cong : ∀ {a} {A : Set a} {xs ys : List A} →
xs ≈-bag ys → length xs ≡ length ys
length-cong = _⇔_.to Fin.isomorphic-same-size ∘ Fin-length-cong
-- All that remains (except for some bookkeeping) is to show that
-- the isomorphism which Fin-length-cong returns relates the two
-- lists.
Fin-length-cong-relates :
∀ {a} {A : Set a} {xs ys : List A} (xs≈ys : xs ≈-bag ys) →
xs And ys Are-related-by Fin-length-cong xs≈ys
Fin-length-cong-relates {xs = xs} {ys} xs≈ys i =
lookup xs i ≡⟨ proj₂ $ to (∈-lookup _) $ to (xs≈ys _) (from (∈-lookup _) (i , refl)) ⟩
lookup ys (proj₁ $ to (∈-lookup _) $
to (xs≈ys _) $
from (∈-lookup _) (i , refl)) ≡⟨ refl ⟩∎
lookup ys (to (Fin-length-cong xs≈ys) i) ∎
where open _↔_
-- We get that the two definitions of bag equivalence are logically
-- equivalent.
≈⇔≈′ : ∀ {a} {A : Set a} {xs ys : List A} → xs ≈-bag ys ⇔ xs ≈-bag′ ys
≈⇔≈′ = record
{ to = λ xs≈ys → record
{ bijection = Fin-length-cong xs≈ys
; related = Fin-length-cong-relates xs≈ys
}
; from = from
}
where
equality-lemma : ∀ {a} {A : Set a} {x y z : A} →
y ≡ z → (x ≡ y) ↔ (x ≡ z)
equality-lemma refl = id
from : ∀ {xs ys} → xs ≈-bag′ ys → xs ≈-bag ys
from {xs} {ys} xs≈ys z =
z ∈ xs ↔⟨ ∈-lookup xs ⟩
∃ (λ i → z ≡ lookup xs i) ↔⟨ Σ-cong (_≈-bag′_.bijection xs≈ys)
(λ i → equality-lemma $
_≈-bag′_.related xs≈ys i) ⟩
∃ (λ i → z ≡ lookup ys i) ↔⟨ inverse (∈-lookup ys) ⟩
z ∈ ys □
------------------------------------------------------------------------
-- Left cancellation
-- We have basically already showed that cons is left cancellative for
-- the (first) alternative definition of bag equivalence.
∷-left-cancellative′ : ∀ {a} {A : Set a} {x : A} xs ys →
x ∷ xs ≈-bag′ x ∷ ys → xs ≈-bag′ ys
∷-left-cancellative′ {x = x} xs ys x∷xs≈x∷ys = record
{ bijection = Fin.cancel-suc (_≈-bag′_.bijection x∷xs≈x∷ys)
; related = Fin.cancel-suc-preserves-relatedness x xs ys
(_≈-bag′_.bijection x∷xs≈x∷ys)
(_≈-bag′_.related x∷xs≈x∷ys)
}
-- By the equivalence above we get the result also for the first
-- definition of bag equivalence, but we can show this directly, with
-- the help of some lemmas.
abstract
-- The index function commutes with applications of certain
-- inverses. Note that the last three equational reasoning steps do
-- not need to be written out; I included them in an attempt to make
-- it easier to understand why the lemma holds.
index-commutes : ∀ {a} {A : Set a} {z : A} {xs ys} →
(xs≈ys : xs ≈-bag ys) (p : z ∈ xs) →
index (_↔_.to (xs≈ys z) p) ≡
_↔_.to (Fin-length-cong xs≈ys) (index p)
index-commutes {z = z} {xs} {ys} xs≈ys p =
(index $ to (xs≈ys z) p) ≡⟨ lemma z p ⟩
(index $ to (xs≈ys _) $ proj₂ $
from (Fin-length xs) $ to (Fin-length xs) (z , p)) ≡⟨ refl ⟩
(index $ proj₂ $ Σ-map P.id (to (xs≈ys _)) $
from (Fin-length xs) $ to (Fin-length xs) (z , p)) ≡⟨ refl ⟩
(to (Fin-length ys) $ Σ-map P.id (to (xs≈ys _)) $
from (Fin-length xs) $ index p) ≡⟨ refl ⟩∎
(to (Fin-length-cong xs≈ys) $ index p) ∎
where
open _↔_
lemma : ∀ z p →
(index $ to (xs≈ys z) p) ≡
(index $
to (xs≈ys (lookup xs (to (Fin-length xs) (z , p)))) $
proj₂ $ from (Fin-length xs) $
to (Fin-length xs) (z , p))
lemma z p with to (Fin-length xs) (z , p)
| Σ-≡,≡←≡ (left-inverse-of (Fin-length xs) (z , p))
lemma .(lookup xs i) .(from (∈-lookup xs) (i , refl))
| i | refl , refl = refl
-- Bag equivalence isomorphisms preserve index equality. Note that
-- this means that, even if the underlying equality is proof
-- relevant, a bag equivalence isomorphism cannot map two distinct
-- proofs of z ∈ xs (say) to different positions.
index-equality-preserved :
∀ {a} {A : Set a} {z : A} {xs ys} {p q : z ∈ xs}
(xs≈ys : xs ≈-bag ys) →
index p ≡ index q →
index (_↔_.to (xs≈ys z) p) ≡ index (_↔_.to (xs≈ys z) q)
index-equality-preserved {z = z} {p = p} {q} xs≈ys eq =
index (_↔_.to (xs≈ys z) p) ≡⟨ index-commutes xs≈ys p ⟩
_↔_.to (Fin-length-cong xs≈ys) (index p) ≡⟨ cong (_↔_.to (Fin-length-cong xs≈ys)) eq ⟩
_↔_.to (Fin-length-cong xs≈ys) (index q) ≡⟨ sym $ index-commutes xs≈ys q ⟩∎
index (_↔_.to (xs≈ys z) q) ∎
-- If x ∷ xs is bag equivalent to x ∷ ys, then xs and ys are bag
-- equivalent.
∷-left-cancellative : ∀ {a} {A : Set a} {x : A} {xs ys} →
x ∷ xs ≈-bag x ∷ ys → xs ≈-bag ys
∷-left-cancellative {A = A} {x} {xs} {ys} x∷xs≈x∷ys z =
⊎-left-cancellative
(x∷xs≈x∷ys z)
(lemma x∷xs≈x∷ys)
(lemma (inverse ∘ x∷xs≈x∷ys))
where
abstract
-- If the equality type is proof irrelevant (so that p and q are
-- equal), then this lemma can be proved without the help of
-- index-equality-preserved.
lemma : ∀ {xs ys} (inv : x ∷ xs ≈-bag x ∷ ys) →
Well-behaved (_↔_.to (inv z))
lemma {xs} inv {b = z∈xs} {a = p} {a′ = q} hyp₁ hyp₂ = ⊎.inj₁≢inj₂ (
inj₁ tt ≡⟨ refl ⟩
index {xs = x ∷ xs} (inj₁ p) ≡⟨ cong index $ sym $ to-from hyp₂ ⟩
index {xs = x ∷ xs} (from (inj₁ q)) ≡⟨ index-equality-preserved (inverse ∘ inv) refl ⟩
index {xs = x ∷ xs} (from (inj₁ p)) ≡⟨ cong index $ to-from hyp₁ ⟩
index {xs = x ∷ xs} (inj₂ z∈xs) ≡⟨ refl ⟩∎
inj₂ (index {xs = xs} z∈xs) ∎)
where open _↔_ (inv z)
-- Cons is not left cancellative for set equivalence.
∷-not-left-cancellative :
¬ (∀ {A : Set} {x : A} {xs ys} →
x ∷ xs ∼[ set ] x ∷ ys → xs ∼[ set ] ys)
∷-not-left-cancellative cancel =
_⇔_.to (cancel (++-idempotent (tt ∷ [])) tt) (inj₁ refl)
-- _++_ is left and right cancellative (for bag equivalence).
++-left-cancellative : ∀ {a} {A : Set a} (xs : List A) {ys zs} →
xs ++ ys ≈-bag xs ++ zs → ys ≈-bag zs
++-left-cancellative [] eq = eq
++-left-cancellative (x ∷ xs) eq =
++-left-cancellative xs (∷-left-cancellative eq)
++-right-cancellative : ∀ {a} {A : Set a} {xs ys zs : List A} →
xs ++ zs ≈-bag ys ++ zs → xs ≈-bag ys
++-right-cancellative {xs = xs} {ys} {zs} eq =
++-left-cancellative zs (λ z →
z ∈ zs ++ xs ↔⟨ ++-comm zs xs z ⟩
z ∈ xs ++ zs ↔⟨ eq z ⟩
z ∈ ys ++ zs ↔⟨ ++-comm ys zs z ⟩
z ∈ zs ++ ys □)
------------------------------------------------------------------------
-- The third definition of bag equivalence is sound with respect to
-- the other two
-- _∷_ preserves bag equivalence.
infixr 5 _∷-cong_
_∷-cong_ : ∀ {a} {A : Set a} {x y : A} {xs ys} →
x ≡ y → xs ≈-bag ys → x ∷ xs ≈-bag y ∷ ys
_∷-cong_ {x = x} {xs = xs} {ys} refl xs≈ys = λ z →
z ≡ x ⊎ z ∈ xs ↔⟨ id ⊎-cong xs≈ys z ⟩
z ≡ x ⊎ z ∈ ys □
-- We can swap the first two elements of a list.
swap-first-two : ∀ {a} {A : Set a} {x y : A} {xs} →
x ∷ y ∷ xs ≈-bag y ∷ x ∷ xs
swap-first-two {x = x} {y} {xs} = λ z →
z ≡ x ⊎ z ≡ y ⊎ z ∈ xs ↔⟨ ⊎-assoc ⟩
(z ≡ x ⊎ z ≡ y) ⊎ z ∈ xs ↔⟨ ⊎-comm ⊎-cong id ⟩
(z ≡ y ⊎ z ≡ x) ⊎ z ∈ xs ↔⟨ inverse ⊎-assoc ⟩
z ≡ y ⊎ z ≡ x ⊎ z ∈ xs □
-- The third definition of bag equivalence is sound with respect to
-- the first one.
≈″⇒≈ : ∀ {a} {A : Set a} {xs ys : List A} → xs ≈-bag″ ys → xs ≈-bag ys
≈″⇒≈ [] = λ _ → id
≈″⇒≈ (x ∷ xs≈ys) = refl ∷-cong ≈″⇒≈ xs≈ys
≈″⇒≈ swap = swap-first-two
≈″⇒≈ (trans xs≈ys ys≈zs) = λ z → _ ↔⟨ ≈″⇒≈ xs≈ys z ⟩ ≈″⇒≈ ys≈zs z
-- The other direction should also be provable, but I expect that this
-- requires some work.